2021
DOI: 10.3390/met11040548
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Alumina Nanofibers Sintered by the Spark Plasma Method on Nickel Mechanical Properties

Abstract: The article presents the study of alumina nanoparticles’ (nanofibers) concentration effect on the strength properties of pure nickel. The samples were obtained by spark plasma sintering of previously mechanically activated metal powders. The dependence of the grain size and the relative density of compacts on the number of nanofibers was investigated. It was found that with an increase in the concentration of nanofibers, the average size of the matrix particles decreased. The effects of the nanoparticle concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…The melting temperatures of the copper and nickel are obtained by a Cu-Ni binary alloy phase diagram of the American Society for Metals (ASM) handbook Volume 3 [1]. The melting temperatures of TiN is obtained as previously shown in a literature [25]. The differences in the Cu ratios of the mixtures of Cu-Ni-TiN electrodes are presented in Table 2.…”
Section: Experimental Procedures 21 Materials Datamentioning
confidence: 99%
See 2 more Smart Citations
“…The melting temperatures of the copper and nickel are obtained by a Cu-Ni binary alloy phase diagram of the American Society for Metals (ASM) handbook Volume 3 [1]. The melting temperatures of TiN is obtained as previously shown in a literature [25]. The differences in the Cu ratios of the mixtures of Cu-Ni-TiN electrodes are presented in Table 2.…”
Section: Experimental Procedures 21 Materials Datamentioning
confidence: 99%
“…At low pressure, chromium particles were better dispersed throughout ten specimens because of the stronger bonding between atoms. In addition, Fonda et al [25] studied the impacts of adding titanium carbide (5-20%) to a copper-tungsten electrode. The results showed that the electrode had the highest density, lowest electric resistivity, highest EDM efficiency, lowest wear rate, and highest material removal rate when 15% titanium carbide was added.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this work, we investigated the effect of small amounts of ZrO 2 and MgAl 2 O 4 nanoparticles, which have Young’s modulus of 577 GPa [ 32 ] and 275 GPa [ 33 ], respectively, on mechanical properties of the NiAl-CrMo matrix. Thermodynamic modeling was carried out in the Terra ® software environment [ 34 ] to predict the phase formation in the NiAl-Cr-Mo system, as well as with a small amount of carbon that enters the matrix from graphite molds during spark plasma sintering [ 35 , 36 ], considering the formation of a regular Cr-Mo solid solution. A fractographic analysis of the obtained samples was carried out, as well as studies of the features of the temperature dependence of internal friction.…”
Section: Introductionmentioning
confidence: 99%